Analisis Resiko Keselamatan Kerja Dengan Metode Hirarc (Hazard Identification, Risk Assessment, And Risk Control) di Tambang Bawah Tanah PT.Nusa Alam Lestari, Desa Salak, Kecamatan Talawi, Kota Sawahlunto, Provinsi Sumatera Barat - Diva Alfaret; Fadhilah Fadhilah (Journals Mining Engineering : Bina Tambang, 2021)
PT. Nusa Alam Lestari is a company engaged in coal mining that implements an underground mining system and has great risks and dangers, so it is necessary to take action to raise awareness of the importance of occupational health and safety at every stage of the activity. Hazards and risks can occur when ventilation installation activities and support installation activities take place, it is necessary to identify potential hazards to obtain data on potential hazards, then carry out weighting to determine control plans that are suitable for conditions Hazard potential analysis and risk control in this study used the hazard identification method, risk assessment and risk control (HIRARC) using the likelihood and saverity parameters to obtain a value for each hazard risk. Data obtained using questionnaires, interviews, and observations of work activities. The results showed that the identified risks in the ventilation installation were 18 potential hazards that might occur. Questionnaire analysis using the HIRARC method found the level of risk in the ventilation installation work, namely moderate risk (moderate risk) 11% with the criteria of slipping and falling while carrying the wind hose in the tunnel and colliding with the tunnel roof support when carrying the wind hose in the tunnel. The identified risks in the installation of supports are 27 potential hazards that may occur. Questionnaire analysis using the HIRARC method found the level of risk in the work of installing the supports, namely high risk (high risk) 4% with the criteria of being hit by hanging rocks when dismantling old supports and moderate risk (medium risk) 11% with the criteria of slipping and falling while transporting wooden supports collided with the support for the roof of the tunnel while transporting the support logs, crushed the support wood when dismantling the old support Meanwhile, the risk control uses the hierarchy of control method, namely elimination, substitution, engineering control, administrative control, and PPE.